1995
DOI: 10.1007/bf00874140
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microbial communities in anaerobic bioreactors using molecular probes

Abstract: The microbial community structure of twenty-one single-phase and one two-phase full-scale anaerobic sewage sludge digesters was evaluated using oligonucleotide probes complementary to conserved tracts of the 16S rRNAs of phylogenetically defined groups of methanogens and sulfate-reducing bacteria. These probe results were interpreted in combination with results from traditional chemical analyses and metabolic activity assays. It was determined that methanogens in "healthy" mesophilic, single-phase sewage sludg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 28 publications
10
85
2
Order By: Relevance
“…In natural environments, M. concilii were the dominant MA in Antarctic sediments (Purdy et al 2003b), chlorinated-solvent contaminated aquifers (Dojka et al 1998), and gas-condensate contaminated aquifers with high levels of sulfate (Struchtemeyer et al 2005). M. concilii were also found to predominate in engineered systems treating sewage or municipal solid waste (Griffin et al 1998;McMahon et al 2001;Raskin et al 1995b;Zheng and Raskin 2000), and industrial effluents (Plumb et al 2001). In one study, M. concilii were found to make up 90% of the archaeal community in an anaerobic digester (Merkel et al 1999).…”
Section: Archaeal Clone Libraries Archaeal Clone Libraries (Figures 4mentioning
confidence: 99%
See 1 more Smart Citation
“…In natural environments, M. concilii were the dominant MA in Antarctic sediments (Purdy et al 2003b), chlorinated-solvent contaminated aquifers (Dojka et al 1998), and gas-condensate contaminated aquifers with high levels of sulfate (Struchtemeyer et al 2005). M. concilii were also found to predominate in engineered systems treating sewage or municipal solid waste (Griffin et al 1998;McMahon et al 2001;Raskin et al 1995b;Zheng and Raskin 2000), and industrial effluents (Plumb et al 2001). In one study, M. concilii were found to make up 90% of the archaeal community in an anaerobic digester (Merkel et al 1999).…”
Section: Archaeal Clone Libraries Archaeal Clone Libraries (Figures 4mentioning
confidence: 99%
“…It was also found that Methanosaeta were the dominant aMA, Methanobacterium were the dominant hMA, and Desulfobulbus was important for propionate degradation. Raskin et al (1995b) analyzed samples from 21 anaerobic sludge digesters. They determined that Methanosaeta were the dominant MA in most samples and Desulfovibrio and Desulfobulbus, both iSRB, were the dominant SRB groups.…”
Section: Molecular Analysis Of Anaerobic Systemsmentioning
confidence: 99%
“…Triplicate samples of a 100-fold dilution of the DNA-samples were analyzed for total bacteria, total archaea and the methanogenic methanogenic populations Methanobacteriales, Methanomicrobiales, Methanosarcinaceae and Methanosaetaceae. Total archaea can be considered a valid estimation of total methanogens in AD, because of the highly unfavourable conditions of nonmethanogenic archaea in AD (Raskin et al 1995, Woese et al 1990). To quantify total bacteria the general bacterial primers P338F (5'-ACTCCTACGGGAGGCAGCAG-3') and P518r (5'-ATTACCGCGGCTGCTGG-3'), as described by Ovreas et al (1997), were used.…”
Section: S5 Real-time Pcr Analysismentioning
confidence: 99%
“…Only a few Desulfobacter species, D. postgatei, D. hydrogenophilus, D. latus, and D. cuwatus, have been validly described (40). Although other members of the Desulfobacter genus have been recently detected, e.g., by oligonucleotide probes, in various locations like bioreactors (33), oil field environments (7, 39), and photosynthetic biofilms (32), none of them has been isolated and characterized.…”
mentioning
confidence: 99%